NGS-PrimerPlex: High-throughput primer design for multiplex polymerase chain reactions - Kechin, Andrey (PLoS Comput Biol, 2020)
Multiplex polymerase chain reaction (PCR) has multiple applications in molecular biology, including developing new targeted next-generation sequencing (NGS) panels. We present NGS-PrimerPlex, an efficient and versatile command-line application that designs primers for different refined types of amplicon-based genome target enrichment. It supports nested and anchored multiplex PCR, redistribution among multiplex reactions of primers constructed earlier, and extension of existing NGS-panels. The primer design process takes into consideration the formation of secondary structures, non-target amplicons between all primers of a pool, primers and high-frequent genome single-nucleotide polymorphisms (SNPs) overlapping. Moreover, users of NGS-PrimerPlex are free from manually defining input genome regions, because it can be done automatically from a list of genes or their parts like exon or codon numbers. Using the program, the NGS-panel for sequencing the LRRK2 gene coding regions was created, and 354 DNA samples were studied successfully with a median coverage of 97.4% of target regions by at least 30 reads. To show that NGS-PrimerPlex can also be applied for bacterial genomes, we designed primers to detect foodborne pathogens Salmonella enterica, Escherichia coli O157:H7, Listeria monocytogenes, and Staphylococcus aureus considering variable positions of the genomes.